Pepper Auction Market Development Strategy in Sleman Regency - Anisah, Siti Afni; Nugroho, Agus Dwi; Waluyati, Lestari Rahayu (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 2 (2020): Vol.14.No 2, 2020, 2020)
The pepper auction market in Sleman Regency was formed in 2017. This market is becoming the main marketing line for all pepper traders in Sleman Regency because it is serving appropriate prices for the farmer. Some problems also appeared during the implementation of the pepper auction market. This study aimed to arrange an effective strategy in developing a pepper auction market in Sleman Regency. This study conducted from January to February 2020 involving 23 major traders who chosen by the census method and 6 stakeholders who chosen by purposive sampling technique. SWOT analysis was applied to arrange an effective strategy in developing the pepper auction market. The result showed that the most effective strategy used in developing the pepper auction market was the SO-Strategy, such as: improving product quantity and quality, improving the quality of services and creating good relationships with the assembly point management party and auction participants, and building an online product and price database system. The auction market management parties and some stakeholders are required to regularly monitor and assure the market system in conducting a market auction process appropriately. We also suggested to use modern technology devices to assure the auction transparency.